Implementasi Program Gerakan Orangtua Mengajar Untuk Meningkatkan Motivasi Belajar Siswa - Diah Rina Miftakhi; Maulina Hendrik (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2018)
This study aims to describe the movement of parents teaching in schools in order to improve the motivation of learners by involving parents in school programs. This program is implemented one of the goals is to reduce the number of school dropouts that occur in coastal areas. This research uses qualitative naturalistic approach. Data collection is done through observation, interview, and documentation. The subjects of this study include principals, teachers, employees, parents of learners and learners. the validity of data is done by triangulation, prolongation of research and observation persistence. The results showed that the implementation of parental teaching movement that has been implemented in SD Negeri 10 Pangkalanbaru very effective implemented. The program that has been implemented is the carier day program. The program is implemented to foster the spirit and motivation and do not experience dropping out and have aspirations to continue their education to a higher level. The parents' tasks of the students in this parenting teaching program is that they are asked to describe and tell the profession all this time they do. The profession will also be associated with the subjects that are learned by the students in the school